2019
DOI: 10.1016/j.neuroimage.2018.09.007
|View full text |Cite
|
Sign up to set email alerts
|

The BOLD response in primary motor cortex and supplementary motor area during kinesthetic motor imagery based graded fMRI neurofeedback

Abstract: There is increasing interest in exploring the use of functional MRI neurofeedback (fMRI-NF) as a therapeutic technique for a range of neurological conditions such as stroke and Parkinson's disease (PD). One main therapeutic potential of fMRI-NF is to enhance volitional control of damaged or dysfunctional neural nodes and networks via a closed-loop feedback model using mental imagery as the catalyst of self-regulation. The choice of target node/network and direction of regulation (increase or decrease activity)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 70 publications
4
35
0
Order By: Relevance
“…These tasks typically involve either motor imagery or finger tapping paradigms (e.g., Berman et al, 2012) and involve primarily upregulation of primary motor or premotor/supplementary motor activity (SMA). However, there are mixed results in this field; for example, the previously cited study from Berman and colleagues found that primary motor cortex regulation was possible during finger tapping but not motor imagery, while Mehler et al (2019) found that neurofeedback was associated with a decrease in primary motor but an increase in SMA engagement activity during motor imagery. Rt-fMRI-NF training focusing on upregulating the SMA during finger tapping and motor imagery is promising for reducing motor symptoms of Parkinson's (Subramanian et al, 2016) Huntington's (Papoutsi et al, 2018), and chronic stroke (Liew et al, 2016).…”
Section: Behavioral Domains Where Neurofeedback Has Been Investigatedmentioning
confidence: 99%
“…These tasks typically involve either motor imagery or finger tapping paradigms (e.g., Berman et al, 2012) and involve primarily upregulation of primary motor or premotor/supplementary motor activity (SMA). However, there are mixed results in this field; for example, the previously cited study from Berman and colleagues found that primary motor cortex regulation was possible during finger tapping but not motor imagery, while Mehler et al (2019) found that neurofeedback was associated with a decrease in primary motor but an increase in SMA engagement activity during motor imagery. Rt-fMRI-NF training focusing on upregulating the SMA during finger tapping and motor imagery is promising for reducing motor symptoms of Parkinson's (Subramanian et al, 2016) Huntington's (Papoutsi et al, 2018), and chronic stroke (Liew et al, 2016).…”
Section: Behavioral Domains Where Neurofeedback Has Been Investigatedmentioning
confidence: 99%
“…This data exclusion compromises significantly the power of the current study, in particular in combination with a second threshold that discards entire runs if more than 30% of volumes are affected. For comparison, we applied the same threshold (FD > 0.5 mm) to existing head motion data acquired from a previous experiment with a similar fMRI-NF paradigm that was conducted in young healthy participants (Mehler et al, 2019b). We found that only ∼3.4% of volumes showed too large motion (compared to 33% for patients in the present study) and that median head motion ranged from 0.10 to 0.25 mm between participants with a group median of 0.15 mm (compared to 0.17-1.19 mm between patients with a group median of 0.32 mm for the present study).…”
Section: Head Motionmentioning
confidence: 99%
“…In particular, while several studies have shown robust SMA activation during kinesthetic motor imagery, it is still unclear whether M1 can be consistently activated. Some motor imagery studies reported significant activation (Sharma et al, 2008), however, fMRI NF studies found non-conclusive results at group level (Chiew et al, 2012;Blefari et al, 2015) and one recent study showed deactivation of M1 during kinesthetic motor imagery-based upregulation training of the SMA and M1 (Mehler et al, 2019). M1 involvement may depend on the subject and the nature of performed motor imagery task and there is no evidence that it is consistently activated, at least in short training protocols (Hétu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the choice of the cortical target of NF training has a critical impact on the rehabilitation outcome. If ipsilesional primary motor cortex (M1) has been suggested to be the most promising target for an efficient motor recovery (Favre et al, 2014), supplementary motor area (SMA) is easier to engage during motor imagery (Sharma et al, 2006;Mehler et al, 2019) than M1 (Berman et al, 2012;Chiew et al, 2012;Blefari et al, 2015) and may play an important role in restoring motor function in more severely affected patients (Di Pino et al, 2014;Plow et al, 2015). In particular, while several studies have shown robust SMA activation during kinesthetic motor imagery, it is still unclear whether M1 can be consistently activated.…”
Section: Introductionmentioning
confidence: 99%